2010
DOI: 10.1501/tarimbil_0000001125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Agro-Residues on Nutritive Value of Pleurotus eryngii (DC. ex Fr.) Quel. var. ferulae Lanzi

Abstract: In this study, the effect of various compost medium on the nutritive value of P. eryngii var. ferulae were determined. Dry matter, moisture, crude ash, protein, fat and organic matter were determined as 91. 7-92.7, 7.3-8.3, 5.4-6.1, 8.5-19.7, 2.5-4.1 and 85.8-86.9% of air-dried weight, respectively. There were no significant differences in crude ash and organic matter content for P. eryngii var. ferulae grown on various agro-residues. Crude protein and fat contents varied significantly, the lowest protein cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…P. ferulae is reported to contain nematicidal metabolites and to have nematicidal activity (Li et al 2007). Some studies of P. ferulae have focused on the production of basidiocarp using agricultural wastes as substrate (Akydz and Yildiz 2007;Kirbag and Akyuz 2008). Punelli et al (2009) reported detection of laccase activity in two Pleurotus spp.…”
Section: Introductionmentioning
confidence: 99%
“…P. ferulae is reported to contain nematicidal metabolites and to have nematicidal activity (Li et al 2007). Some studies of P. ferulae have focused on the production of basidiocarp using agricultural wastes as substrate (Akydz and Yildiz 2007;Kirbag and Akyuz 2008). Punelli et al (2009) reported detection of laccase activity in two Pleurotus spp.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, the most common substrate used for growing oyster mushrooms is wheat and rye straw, which are easily accessible and not troublesome to prepare. In countries with a warmer climate such as Japan, Korea, and China, P. eryngii is cultivated on sawdust of Japanese cedar, or ground corncobs supplemented with bran, and contained in polypropylene bottles (Akyüz & Kirbağ, 2010;Beetz & Kustudia, 2004;Yamanaka, 2011). The most commonly used substrates include oak, beech, poplar, alder, birch, wild cherry, mango, and elm sawdust (Kwon & Kim, 2004).…”
Section: Practical Applicationsmentioning
confidence: 99%
“…For yielding, air temperature was maintained at 15°C ± 1°C and relative humidity at 85%-90%. The cultivation was additionally Gąsecka et al (2015), Gençcelep, Uzun, Tunçtür, and Demirel (2009), Manzi, Gambelli, Marconi, Vivanti, and Pizzoferrato (1999), Rodriguez-Estrada and Royse (2007), Siwulski et al (2017) K 15 300-40 540 Akyüz and Kirbağ (2010), Gençcelep et al (2009), Guo, Lin, and Lin (2007), Manzi et al (1999), Rodriguez-Estrada and Royse (2007) Mg 1 000-2 000 Gençcelep et al (2009), Guo et al (2007) 2010…”
Section: Substrate Preparation and Experiments Designmentioning
confidence: 99%